2018
DOI: 10.1038/s41467-018-04321-6
|View full text |Cite
|
Sign up to set email alerts
|

Nanographenes as electron-deficient cores of donor-acceptor systems

Abstract: Conjugation of nanographenes (NGs) with electro-active molecules can establish donor-acceptor π-systems in which the former generally serve as the electron-donating moieties due to their electronic-rich nature. In contrast, here we report a series of reversed donor-acceptor structures are obtained by C–N coupling of electron-deficient perchlorinated NGs with electron-rich anilines. Selective amination at the vertexes of the NGs is unambiguously shown through X-ray crystallography. By varying the donating abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 46 publications
0
19
0
1
Order By: Relevance
“…Apart from the electronic effect upon chlorination, it also provides a new entry to the functionalization and derivatization of nanographene molecules. For instance, Tan et al [237] demonstrated selective amination at the vertexes of the chlorinated nanographene molecules 157 and 159 through palladium-catalyzed Buchwald-Hartwig C-N cross-couplings ( Figure 33). The resulting structures 163 and 164 were revealed by X-ray crystallography, representing a new type of donor-acceptor nanographene molecules, of which the optical and assembly properties can be finely modulated by varying the anilino groups.…”
Section: Edge Functionalizationmentioning
confidence: 99%
“…Apart from the electronic effect upon chlorination, it also provides a new entry to the functionalization and derivatization of nanographene molecules. For instance, Tan et al [237] demonstrated selective amination at the vertexes of the chlorinated nanographene molecules 157 and 159 through palladium-catalyzed Buchwald-Hartwig C-N cross-couplings ( Figure 33). The resulting structures 163 and 164 were revealed by X-ray crystallography, representing a new type of donor-acceptor nanographene molecules, of which the optical and assembly properties can be finely modulated by varying the anilino groups.…”
Section: Edge Functionalizationmentioning
confidence: 99%
“…This strategy has also been applied in the preparation of B,N‐containing polycyclic aromatic hydrocarbons such as 25 , which are of potential relevance for implementation in optoelectronic devices. Additionally, the amination of the vertexes of well‐defined nanographenes provided an entry to reversed donor‐acceptor conjugates such as 26 , whose electron‐deficient cavity can host electron‐rich guests as a result of intermolecular charge transfer. In a different example, the sixfold Buchwald–Hartwig amination of a 9,10‐diaminoanthracene derivative with 1,4‐dibromobenzene afforded hexaaza[1 6 ]paracyclophane 27 .…”
Section: Recent Applicationsmentioning
confidence: 99%
“…We began our study by investigating the assembly in solution between 1 and 2 a (Figure ). 2 a shows a double‐concave structure with an electron‐deficient inner core owing to the presence of peripheral chlorines, and thus 2 a is both geometrically and electronically suitable for assembly with electron‐rich buckybowls. As expected, 1 H NMR measurement indicated that mixing 1 with equimolar 2 a in solution caused its sole proton signal (H a ) to shift upfield by 0.11 ppm (Figure ).…”
Section: Figurementioning
confidence: 99%
“…However, this requires structural modification of the buckybowl and could affect its ability to undergo bowl inversion . On the other hand, the electron deficiency of 2 can be weakened by enhancing the electron‐donating ability of its peripheral anilino groups without altering its inner core geometry . In our current study, as the electron deficiency of the nanographene core decreases from 2 a to 2 d , the NMR shift of the complexed 1 relative to that of pure 1 also decreases from 0.11 to 0.08 ppm (Figure ).…”
Section: Figurementioning
confidence: 99%